Balloon versus bougie for dilatation of benign oesophageal strictures - McCain, R Scott (Cochrane Database Syst Rev, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To undertake a systematic review comparing the safety and efficacy of balloon dilatation with bougienage for dilatation of benign oesophageal strictures.